An analytical-numerical approach to simulate the dynamic behaviour of arbitrarily laminated composite plates - Nallim, Liz (2008)
A general analytical-numerical approach developed for the dynamical analysis of unsymmetrically laminated plates of general quadrilateral planforms is presented in this work. An arbitrary quadrilateral thin flat laminate is mapped onto a square basic one, so that a unique macro-element is constructed for the whole plate. The Ritz method is applied to evaluate the governing equation in which the coupling effects of bending and stretching are contained. All possible transverse boundary conditions combining with the different in-plane constraints are considered in the analysis. The resulting algorithm possesses great flexibility, it is easy to program and it needs minimal input information. For these reasons, the proposed methodology results convenient for large scale structural design and analysis where repeated calculations are often required. © 2007 Elsevier Ltd. All rights reserved.